HUBUNGAN PENGETAHUAN TERHADAP TINDAKAN TIDAK AMAN PADA PEKERJA WORKSHOP DI PT BUKAKA TEKNIK UTAMA BALIKPAPAN - Fuadi, Yan; Swandito, Adji; Rusba , Komeyni; Fadillah , Nur (IDENTIFIKASI, 2022)
Bukaka Teknik Utama Balikpapan was founded on November 21, 2000 with a temporary office on Jl. Milono Gunung Sari Village - Central Balikpapan is a business unit of PT. Bukaka Teknik Utama which is engaged in Engineering, Fabrication, Construction Offshore & Onshore and Maintenance Services. In 2005 PT. Bukaka Teknik Utama Balikpapan Branch established an office & workshop on Jl Mulawarman KM 21 Manggar - East Balikpapan. This company has a workforce of 711 people. So many potential hazards that can occur during remanufacturing work. Based on the PPS finding data that has been carried out in the last 3 months, the washing engine area is in first place with the most findings, namely five unsafe behaviors. The five unsafe behaviors include positioning and body movement, risk of un-ergonomic positions, not using PPE, holding objects and reaching and grabbing objects. Of the 55 samples of the knowledge level of PT Bukaka Teknik Utama Workshop workers in the high category, there were 49 workers (89.1%). And the results of research on workers' knowledge of unsafe behavior have a strong relationship. In the unsafe actions of workers, the most dominant category was the safe category, namely 51 respondents (93%).